2008
DOI: 10.1007/s10964-008-9346-z
|View full text |Cite
|
Sign up to set email alerts
|

It Takes a Village: Protecting Rural African American Youth in the Context of Racism

Abstract: Prior research demonstrates negative consequences of racism, however, little is known about community, parenting, and intrapersonal mechanisms that protect youth. Using a mixed-methods approach, this study illuminated linkages between positive and negative contextual influences on rural African American adolescent outcomes. Quantitative results provide support for Structural Ecosystems Theory, in that the influence of discrimination and collective socialization on adolescent outcomes was mediated by racial soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
114
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(118 citation statements)
references
References 36 publications
(53 reference statements)
4
114
0
Order By: Relevance
“…Perceived discrimination has been shown to be uncorrelated with adolescents' racial identities. In addition, a positive correlation has been found between perceived discrimination and self-image, indicating that, as adolescents reported more experiences with discrimination, they also tended to report a better self-image (Berkel et al, 2009). In addition to causing a boost in self-image, perceptions of discrimination have also been shown to positively affect self-pride.…”
Section: "Defense" Mechanismsmentioning
confidence: 96%
See 2 more Smart Citations
“…Perceived discrimination has been shown to be uncorrelated with adolescents' racial identities. In addition, a positive correlation has been found between perceived discrimination and self-image, indicating that, as adolescents reported more experiences with discrimination, they also tended to report a better self-image (Berkel et al, 2009). In addition to causing a boost in self-image, perceptions of discrimination have also been shown to positively affect self-pride.…”
Section: "Defense" Mechanismsmentioning
confidence: 96%
“…In addition to causing a boost in self-image, perceptions of discrimination have also been shown to positively affect self-pride. In facing frequent discriminatory events, some youth feel as if they are being "truly socialized" into their own ethnic/racial group and are really beginning to understand what it means to be members of marginalized groups (Berkel et al, 2009).…”
Section: "Defense" Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing peer support for minority youth in middle school may require educators to target social issues of peer acceptance for these students. Minority students may experience discrimination from peers in middle school (Berkel et al, 2009). Additionally, Hamm, Lambert et al (2013) found that African American male students who affiliated with peer groups with norms favoring effort and achievement were less admired by peers at the end of the school year than at the beginning of the year.…”
Section: Positive Perceptions Of the Middle School Transitionmentioning
confidence: 99%
“…The prevalence of the types of R/ES therefore may not be as important as how well these types of R/ES differentially mediate the stress associated with racial encounters. There is research to support the mediating role of R/ES (Bentley et al 2009;Berkel et al 2009;Hughes et al 2009;Neblett et al 2008). Because these encounters can be positively or negatively stressful, the appraisal of the detriment and intensity of that stress is subjective but highly dependent upon one's exposure, experience and socialization surrounding racial/ethnic politics.…”
Section: Introductionmentioning
confidence: 99%